ANAXAM @ TOMCAT 2.0: easy access to cutting-edge tomographic microscopy for industry - Margie P. Olbinado; Vladimir Novak; Christian Gruenzweig; Anne Bonnin; Federica Marone; Christian Matthias Schlepuetz; Goran Lovric; Marco Stampanoni (e-Journal of Nondestructive Testing)
TOMCAT is a tomographic microscopy beamline at the Swiss Light Source (SLS) of the Paul Scherrer Institut (PSI) [1]. For almost two decades, TOMCAT has been offering its cutting-edge tomographic microscopy capabilities to various industries in need of non-destructive, non-invasive, volumetric, and functional material characterization beyond what is currently possible with conventional X-ray tubes [2]. Five years ago, PSI (together with two Swiss institutes and the Canton of Aargau in Switzerland) has co-founded ANAXAM – a technology transfer center that facilitates the use of advanced analytical methods at large-scale facilities such as the SLS for industrial applications. A collaboration between TOMCAT and ANAXAM has leveled up the imaging capabilities that can be offered to industry. One of the main advantages is that ANAXAM has enabled speedy realizations of necessary sample environments that can be used during synchrotron X-ray tomographic microscopy experiments. In this paper, we show examples of successful investigations performed for several industries such as medical technology, pharmaceuticals, marine industry, automotive, and food [3, 4]. In September 2023, TOMCAT paused its operation to allow for the construction of the new SLS 2.0 storage ring [5] in combination with several beamline upgrades [6]. SLS 2.0 is expected to resume operation mid 2025 with a significantly improved machine performance such as smaller source size, improved beam collimation and higher intensity. TOMCAT 2.0 will leverage on the higher brilliance of SLS 2.0 by deploying its upgrade program on two beamlines: (1) I-TOMCAT will be a brand-new instrument based on an insertion device of the latest generation; and (2) S-TOMCAT, the original beamline, will be refurbished with a new high-field superconducting 5T bending magnet. Here we discuss overall possibilities of TOMCAT 2.0 and ANAXAM with respect to industrial applications.